Dark Places - Flynn, Gillian 1971- (New York Broadway Paperbacks, 2010)
After witnessing the murder of her mother and sisters, seven-year-old Libby Day testifies against her brother Ben, but twenty-five years later she tries to profit from her tragic history and admit that her story might not have been accurate.
Keywords: Children of murder victims -- Fiction; Families -- Fiction -- Crimes against; Juvenile homicide -- Fiction; Brothers and sisters -- Fiction; Kansas City (Mo.) -- Fiction; Suspense fiction